Vulvar Paget Disease: a series of cases in southern Brazil - Marcella B. Persiano; Elisa T. Rosin; Giovana A. Cabrera; Fernanda Uratani; Leticia V. Pires; Felipe Luzzatto; Kathleen M. Schmeler; Mila P. Salcedo (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Vulvar Paget's disease is rare and manifests clinically as erythematous itchy skin lesion with areas of hyperkeratosis. The current report describes the diagnosis, management and outcomes data from a case series of women diagnosed with vulvar Paget's disease in a tertiary hospital in southern Brazil. # Methods A retrospective review of medical records of women with vulvar Paget's disease at a single institution in the period 2000-2020 was carried out. Fisher's exact test was used to compare recurrence in relation to the status of surgical margins after primary treatment and in relation to the surgical modality. Quantitative variables were described using mean and categorical variables using absolute and relative frequencies. # Results Ten patients were identified with the diagnosis of vulvar Paget's disease and two of them were excluded due to lack of information in medical records, therefore eight patients are described. The majority of the patients self-identified as white (87,5%, 7/8) and the median age at diagnosis was 65 years (range 45-81). The most common clinical symptoms were vulvar pruritus (62.5%, 5/8) and burning (37.5%, 3/8). It was not possible to identify the type of initial surgery in three patients, as they started follow-up at the institution after undergoing primary treatment at other institutions. The remaining five patients underwent surgery as their primary treatment -- simple vulvectomy (60%, 3/5) and radical vulvectomy (40%, 2/5). In total, 75% (6/8) of patients had disease recurrence. Radiotherapy and imiquimod were used at the time of recurrence in three patients (50%, 3/6), but surgery remained the most common treatment for recurrence (83%, 5/6). The margin status of surgical specimens from patients starting treatment at the institution was negative in four (80%, 4/5) and positive in one woman (20%, 1/5). There was no significant difference in recurrence rates in patients with negative or positive margins, nor in relation to the surgical modality of the primary treatment. There were two deaths (25%, 2/8), one of them due to complications from Paget's disease and the other one due to metastatic urothelial adenocarcinoma. # Conclusions Vulvar Paget's disease has a significant morbidity and limited data are available, especially in Brazil. Due to the rarity of the disease, no randomized clinical trials are available in the literature and therefore it is difficult to compare the results of surgical treatment and other therapeutic modalities. There is an opportunity to explore best options for adequate Paget's disease treatment.